PERSPECTIVE TRANSPORT-POWER SYSTEM BASED ON THE INTEGRATION OF MAGLEV-TECHNOLOGY AND DISTRIBUTED PHOTO-ELECTRIC STATION - Dzenzerskiy, V. O.; Gnilenko, A. B.; Plaksin, S. V.; Pogorelaya, L. M.; Shkil, Y. V. (Science and Transport Progress, 2018)
Purpose. The research main purpose is the perfection of magnetolevitating technology on electrodynamic suspension and providing its functioning on the base of ecologically rational energy systems. It means creation of the MAGLEV transport-power system which uses renewable energy sources (in particular, photoelectric converters) and is connected to national/local networks as an energy user and producer simultaneously. Methodology. Conducted research, analysis and summary conclusions are based both on the results of works on the given subject, and own works of authors. The methods of systems analysis and computer design of components of the large cyber-physical transport-power system were used during research conducting. Findings. The physical-technical foundations of conception of the perspective transport-power system, which includes high-speed ground vehicle on electrodynamic suspension and distributed photo-electric energy complex are developed. The adapt to the performance of the given transport type and guaranteeing its safe functioning in any weather terms. Originality. For the first time authors substantiated the possibility for creation of single transport complex uniting the speed magnetolevitating system and distributed power supply system on the base of sun energy. It is simultaneously the inalienable part of the precision fast-acting control system, working in the real-time mode. Practical value. The offered scientific-technical solution allows on the base of renewable energy source to solve the problems of power supply and a high-speed transport control. Due to the inclusion of the distributed power supply system into local intellectual networks on the SMART-grid technology it gives the possibility to optimize energy consumption of territories neighboring to high-speed way.